LITERASI AGAMA ISLAM SEBAGAI STRATEGI PEMBINAAN KARAKTER RELIGIUS SISWA RA KM AL HIKMAH KEDIRI - Maimunatun Habibah; Siti Wahyuni (Universitas Islam Lamongan, 2020)
Strengthening religious character as a shield from immorality is important to instill from an early age. Various efforts can be used for this purpose, one of which is through the Islamic literacy movement. This study seeks to reveal the Islamic literacy practice in fostering the religious character of students in RA KM Al-Hikmah through qualitative research methods with a single case study approach. The results of this study find the fact that religious character development is carried out through the practice of Islamic literacy that is integrated in classroom-based learning and school-based culture. Through learning activities that are subject to the content of religious material and delivered with various methods, religious values are not only oriented towards the accumulation of student knowledge but also become a habit to be religious. Another factor that supports the maximization of religious character development for students is the construct of school culture that leads to the formation of religious culture by programming religious activities that are directly related to classroom learning.